Mixed training programs applied to young soccer players: Effects on speed-power abilities - Freitas, T. T.; Pereira, L. A.; Alcaraz, P. A.; Azevedo, P. H. S. M.; Zanetti, V.; Pantarotto, N. B.; Reis, V. P.; Jeffreys, I.; Loturco, I. (International Journal of Sports Medicine, 2023)
We compared the effects of two 4-week strength-power-speed training protocols on physical performance of young soccer players. Twenty-three highly trained under-20 soccer players were randomly allocated to two mixed-training groups: 1) "traditional" (TRAD: n=11), comprising vertically oriented strength-power exercises and linear sprints; or 2) "multidirectional" (MULTI: n=12), combining vertically and horizontally oriented strength-power exercises, linear sprints, and change-of-direction (COD) drills. Squat jump (SJ) and countermovement jump, 2) linear sprint, COD speed, and 3) jump-squat (JS) and hip-thrust (HT) power tests were performed pre- and post-training. Differences were determined using a two-way ANOVA with repeated measures and "target scores" were used to detect real changes in performance. No group-time interactions were found for any of the variables (p>0.05). Significant increases (p<0.05) in 20-m sprint velocity, JS- and HT-power were found in both groups, and in SJ in TRAD. Individual analyses revealed a greater number of meaningful changes in zig-zag velocity in MULTI while most players in TRAD displayed meaningful increases in SJ height. In conclusion, both training protocols resulted in similar adaptations but, at the individual level, it appears that MULTI protocol is superior to improve COD ability while TRAD should be preferred to maximize vertical jumping capabilities during short soccer pre-seasons.